The Power of Discarded Books - Komnenović, Dora (Otrok in knjiga, 2025)
As counterintuitive as it may seem at the first sight, libraries do not only hoard items, they also have to discard parts of their collection from time to time. The process is usually a below-the-radar affair, unless carried out massively and/or inappropriately. It is precisely such instances that make it interesting to examine beyond the field of library science. I in fact argue that the so-called “wild” discarding (also known as “cleansing”) taking place in times of social and political upheaval, together with public reactions to it (or a lack thereof), can provide insights into how communities renegotiate identities and deal with their past. Current reports from Ukraine or from Croatia and Germany three decades ago of libraries withdrawing “unwanted” literature also show that (physical) books still possess an intrinsic and symbolic value despite the declining interest in literary reading, a value that the act of discarding only further enhances ...